The Effect of Sintering Program on the Compressive Strength of Zirconia Copings - Amir Ali Reza Khaledi; Mahroo Vojdani; Mitra Farzin; Soudabeh Pirouzi (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Considering the limitations of conventional sintering of zirconium oxide (ZrO2) copings, shortening the sintering time can be proposed as an alternative method for making the copings. Purpose: This study aimed to assess the effects of sintering time on compressive strength of Yttria Tetragonal Zirconia Polycrystal (Y-TZP) copings. Materials and Method: Thirty copings of pre-sintered 3Y-TZP blanks were milled and sintered in a special furnace for three different durations (n=10 per group). The sintering time was 1 h 15 min for IPS e.max ZirCAD, 4 h 20 min for Speed ZrO2, and 7 h 20 min for the conventional ZrO2 group. The specimens were cemented on the brass dies by using conventional glass ionomer cement. The copings were vertically loaded until fracture by using a universal testing machine. The data were analyzed through one-way analysis of variance (ANOVA) and post hoc test to compare the mean differences of compressive strength yielded in three study groups (α=0.05). Results: The mean ± SD of compressive strength value was (3617 ± 543.54) N for IPS-e.maxZirCAD group, (2663 ± 508.11) N for Speed ZrO2 group, and (1662± 466.71 N) for conventional ZrO2 group. There were statistically significant differences among compressive strength values of the tested groups (p< 0.05). The highest compressive strength values were obtained from the IPS e.max ZirCAD group. Conclusion: Within the limitations of this in vitro study, it can be concluded that compressive strength of the zirconia copings is affected by the sintering time. High compressive strength of zirconia copings can be obtained by shortening the sintering time.